Dissociation between two aspects of procedural learning in Tourette syndrome: Enhanced statistical and impaired sequence learning. Issue 6 (18th August 2021) - Tóth-Fáber, Eszter; Tárnok, Zsanett; Janacsek, Karolina; Kóbor, Andrea; Nagy, Péter; Farkas, Bence Csaba; Oláh, Szabina; Merkl, Dóra; Hegedűs, Orsolya; Nemeth, Dezso; Takács, Ádám
ABSTRACT: Tourette syndrome (TS) is a childhood-onset neurodevelopmental disorder that primarily affects the cortico-basal ganglia-thalamo-cortical (CBGTC) circuitry and is characterized by motor and vocal tics. Previous studies have found enhancement in procedural memory, which depends on the CBGTC circuitry and plays an important role in the learning and processing of numerous motor, social, and cognitive skills and habits. Based on these studies, procedural hyperfunctioning in TS has been proposed. However, the neurocognitive mechanism underlying such hyperfunctioning is poorly understood. Here, we investigated how two aspects of procedural learning, namely 1) frequency-based statistical learning and 2) order-based sequence learning, are affected in TS. Twenty-one children with TS between the ages of ten and fifteen as well as 21 typically developing controls were tested on a probabilistic sequence learning task that enables the parallel assessment of these two aspects. We found that children with TS showed enhanced sensitivity to statistical information but impaired sequence learning compared to typically developing children. The deconstruction of procedural memory suggests that procedural hyperfunctioning in TS may be supported by enhanced sensitivity to statistical information. These results can provide a potential path for improving therapy methods and skill-oriented educational programs for TS.